Pakistan : From 1947 to the Creation of Bangladesh - Charles Scribner's Sons (New York Keesing's Publications (Longman Group Ltd.), 1973)
It covers the tenure from 1947 to the creation of Bangladesh.
Include Maps, Appendices and Index.
Keywords: Pakistan -- Politics and government